Penerapan Teori Gestalt Wolfgang Kohler dalam Meningkatkan Pemahaman Siswa - Puspita, Atha Candra; Ismail, Sachiko Aqila Naila (CV. Lentera Literasi Indonesia, 2025)
This study analyzes the application of Gestalt theory, especially the concept of insight learning developed by Wolfgang Kohler, in an effort to improve student understanding in the learning process. Gestalt theory views that learning is not just about stimulus and response, but rather emphasizes a thorough understanding of a problem so as to be able to produce new insightful conclusions. Wolfgang Kohler, as one of the important figures of Gestalt theory who is famous for his research on insight in chimpanzees, made a significant contribution to the development of an understanding-based learning approach. This research implements Gestalt learning principles such as learning through insight, meaningful learning, and learning interaction. The research methodology uses literature review by comparing various reference sources related to the Application of Wolfgang Kohler's Gestalt Theory in Improving Student Understanding. The results showed that the application of Wolfgang Kohler's Gestalt theory significantly improved students' ability to understand the relationship between parts in the material, can capture the basic principles and apply them in different contexts. However, this study also found that Gestalt theory has limitations in its application to certain abstract topics.